THE IMPACT OF ARTIFICIAL INTELLIGENCE ON STUDENTS’ INTEREST AND ACHIEVEMENT IN LEARNING MATHEMATICS: Bengkulu, Indonesia - Sarwoedi; Syamsir; Muhammad Sholihin; Deri Wanto; Idi Warsah (Jurnal Math-UMB.EDU, 2025)
This study investigates the impact of Artificial Intelligence (AI) on students’ interest and achievement in learning mathematics compared to the use of printed textbooks. A quasi-experimental design was employed with two groups of senior high school students: the experimental group utilized AI-based applications, while the control group relied on printed textbooks as the main learning resource. Research instruments included a learning interest questionnaire, achievement tests, and classroom observations. The results indicate that students learning with AI demonstrated higher levels of interest due to interactivity and personalized content. Furthermore, there was a significant difference in learning outcomes between the AI group and the textbook group. The findings suggest that integrating AI into mathematics instruction can serve as an innovative strategy to foster student motivation and improve academic performance, while printed textbooks remain valuable as supplementary learning resources. Keywords: Artificial Intelligence, learning interest, learning outcomes, mathematics